Analysis and Design of Web-Based Inventory Receipt and Management Information Systems at Heycaps.Co Stores Using the Prototype Method - Ni Putu Tia Ananda; Putri, I Gusti Agung Pramesti Dwi; Kusuma, Ni Putu Noviyanti (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
Effective inventory management is crucial for Heycaps.co to ensure smooth operations and customer satisfaction. However, the current manual system results in inventory data inconsistencies, delays in the receipt of goods, and challenges in inventory tracking. This study aims to design a web-based inventory receipt and management information system to address these issues. The system is developed using a prototype approach, incorporating Flowcharts, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), Table Relations, and Database Table Structures. The interface design employs the Bootstrap framework to ensure a responsive and user-friendly display. The findings of this study present a system design that can be utilized by the owner, warehouse staff, and store staff to enhance inventory data management, streamline the receipt process, and improve the accuracy of inventory reporting. User evaluations indicate that the proposed system meets user requirements and offers ease of use. Keywords: Information System, Inventory, Prototype Method, Heycaps.co, Inventory  Management.